Detection of the YMDD Motif Mutations Rate in Chronic Hepatitis B Patients Treated with Lamivudine - Soudbakhsh A (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2011)
Background and Objectives: Lamivudine is the first nucleoside analogue licensed for the treatment of chronic hepatitis B patients which is effective in suppressing virus replication and results in reduced disease activity. However the most important problem of lamivudine treatment is the emergence of lamivudine resistance strains with amino acid substitution in the YMDD motif of the DNA polymerase during the treatment. The aim of this study was to evaluate the frequency of YMDD motif mutations in chronic hepatitis B patients treated with lamivudine. Methods: 56 chronic hepatitis B patients who had not previously received interferon and/or a nucleoside/nucleotide analogue, received lamivudine for a minimum of 6 months were examined in this study. HBV DNA was extracted from serum samples, and YMDD mutations in the HBV DNA polymerase gene was determined using PCR-direct sequencing. HBV DNA quantification was determined using real-time PCR. Results: 56 patients 39 (69.6%) male and 17 (30.4%) female with mean age of 34.12±) 13.6 (were evaluated. YMDD motif mutations were observed in 15 out of 56 patients (26.7%). 8 of these mutations (14.2%) were in the form of YIDD and the remaining 7 (12.5%) in YVDD form. Serine mutation at YMDD motif was not found in this study.Conclusion: YMDD motif mutations leading to lamivudine resistance is common in our chronic hepatitis B patients. Molecular diagnosis of YMDD motif mutations using methods such as direct DNA sequencing can detect upcoming viral resistance in chronic hepatitis B patients.